A polypyrrole solution in chloroform - Lee, J.Y.; Kim, D.Y.; Song, K.T.; Kim, S.Y.; Kim, C.Y. (Taylor and Francis Inc., 1996)
Polypyrrole(PPy) soluble in chloroform and m-cresol was chemically synthesized by using ammonium persulfate as an oxidant and dodecylbenzene sulfonic acid as a dopant source. Electrical conductivity of resulting PPy becomes higher when polymerized with higher concentration of the oxidant and at lower polymerization temperature. The surface of PPy film cast from the solution is so smooth to give little scattering but total reflection and the film shows electrical conductivity of 4.5 S/cm. PPy solution in chloroform shows much greater absorption in the free carrier-tail region than that in m-cresol does, indicating that chloroform is a better solvent. The cast film sustains the cyclic redox reactivity for more than 100 cycles in the system of tetrabutylammonium dodecylsulfate in acetonitrile.